The Liar Speaks the Truth : a Defense of the Revision Theory of Truth. - Yaqub, Aladdin M. (Oxford University Press, 1993)
The concept of truth has been the focus of much attention in philosophical literature, but has resisted adequate explanation. This study explores a "deflationary" or "minimalist" account of truth that can account for the challenge posed by semantic paradoxes such as the liar.